REAKSI PASAR SAHAM INDONESIA TERHADAP INVESTASI TEKNOLOGI INFORMASI BERDASARKAN KARAKTERISTIK INVESTASI TEKNOLOGI INFORMASI DAN PERUSAHAAN - Haryadi Indrianto Nugroho (ABIS: Accounting and Business Information Systems Journal, 2013)
The rapid development of information technology affects almost every aspect of life, including the business world. Firms vigorously implement the most advanced information technology to improve firm performance.The big question to be answered by this study is whether the investment in information technology really has an impact on the firm. Impact on the firm can be measured through the firm's improved performance, as represented by the increase in the firm’s value. The value of the firm's shares will be adjusted, based on firm characteristics and the characteristics of the investment at the time of the announcement of the investment. The impact of information technology investment will be different in each firm, because every firm has different characteristics.The results of this study indicate that, in general, information technologyinvestment announcements do not have a significant effect on abnormal stock returns. This suggests that for the time being, the decision of investors in Indonesia are not so influenced by information technology investments made by the firm. Investors in Indonesia do not believe that the investment in information technology can provide added value to the firm in the future. However, for information technology investments with particular characteristics, which are made by companies with specific characteristics, can affect stock returns. Interaction effects can give explain variables that moderate the relationship between information technology investment announcements and market reaction.One of the contribution of this study is to provide an overview for managers who intend to invest in information technology. Companies with certain characteristics can leverage these investments as a means to communicate the business strategy to investors, with the aim to enhance shareholder value.